Digital Leadership dan Transformasi Digital dalam Mendorong Kinerja Organisasi Publik Islami - Hamzah, Mohammad (Assyarikah: Journal of Islamic Economic Business, 2025)
This study aims to examine the effect of digital leadership on organizational performance in the public sector, with digital transformation as a mediating variable. The research is motivated by the practical issue of low effectiveness in digital technology implementation within local government bureaucracies, despite the availability of infrastructure. A quantitative approach was applied to 135 employees from various local government agencies, using a structured questionnaire for data collection. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM). The results indicate that digital leadership significantly affects digital transformation, and digital transformation positively impacts organizational performance. However, the direct effect of digital leadership on organizational performance is not significant, confirming a full mediation effect. These findings emphasize the critical role of digital transformation as a strategic link between technology-based leadership and performance outcomes. Theoretically, this research underscores that successful digital adoption in the public sector requires leaders who can drive transformation effectively. Practically, the findings provide a foundation for local governments to design integrated policies for strengthening digital leadership and advancing bureaucratic transformation.